IGF-1R Inhibition Suppresses Cell Proliferation and Increases Radiosensitivity in Nasopharyngeal Carcinoma Cells. (31st July 2019) - Wang, Zhe; Liu, Guangyan; Mao, Jiwei; Xie, Min; Zhao, Ming; Guo, Xuefen; Liang, Shanshan; Li, Heming; Li, Xuefeng; Wang, Ruoyu
Abstract : Although ionizing radiation (IR) has provided considerable improvements in nasopharyngeal carcinoma (NPC) treatment, radioresistance is still a major threat for some subsets of patients. The insulin-like growth factor-1 receptor (IGF-1R) signaling pathway is tightly regulated and plays critical roles in mediating cell proliferation, growth, and survival. Thus, IGF-1R may be a potential therapeutic target for patients with different malignancies. However, its mechanism in NPC is not fully investigated. Linsitinib is an oral small molecule and is a tyrosine kinase inhibitor (TKI) of IGF-1R, which has been known for antitumor effects used widely. Here, we evaluated the proliferation and radiosensitivity of NPC cell lines (CNE-2 and SUNE-1) after linsitinib treatment. We found that linsitinib suppresses IGF-1-induced cell proliferation through inhibiting Akt and ERK phosphorylation. Moreover, linsitinib further boosted IR-induced DNA damage, G2-M cell cycle delay, and apoptosis in NPC cells. Finally, linsitinib reversed radioresistant NPC cells by decreasing the phosphorylation of IGF-1R. Our data indicated that the combination of linsitinib and IR and targeting IGF-1R by linsitinib could be a promising therapeutic strategy for NPC.